Scaling of Different Innovations from SI-MFS (WP4) - Ahmed, S.; Miajy, Abdullah; Debnath, Manik; Haque, Abudul; Bhandari, Humnath (International Rice Research Institute, 2023)
The SI-MFS initiative in Bangladesh working on different innovations such as intensifying and diversifying cropping systems for better crop-livestock integration, intensifying and diversifying homestead gardens for improved nutrition, and sustainable intensification of livestock production within MFS. Under these initiatives, SI-MFS has done several scaling activities in 2023.